A implementação do serviço de tradução e interpretação em Língua Brasileira de Sinais e Língua Portuguesa no Tribunal de Justiça do Tocantins - Alves, Alini Cardoso de Albuquerque (2024)
This study analyzes the implementation of translation and interpretation services in Brazilian Sign Language (Libras) and Portuguese at the Court of Justice of Tocantins (TJTO). Considering the fundamental right to access justice, the research is justified by the need for public policies that ensure the rights of deaf individuals, aiming to promote inclusion and equal opportunities. The general objective of this research is to describe the trajectory of the implementation of translation and interpretation services in Brazilian Sign Language and Portuguese at the Court of Justice in the state of Tocantins. The research objectives include describing the process of implementing TILSP (Translation and Interpretation in Libras and Portuguese) services at TJTO, identifying the challenges faced during the systematization process, and the current challenges in maintaining and improving translation and interpretation services.Additionally, the study seeks to describe the professional profile of the Libras and Portuguese translators and interpreters working at TJTO, as required in the accreditation notices. By gaininga deeper understanding of the demands and obstacles encountered during this implementation process, it is hoped that this study will contribute to the development of policies and practices that promote equity for deaf individuals within the Brazilian judicial system, as well as understanding the impacts this has had on ensuring the rights of the deaf community. The research is based on previous studies on Libras translation and interpretation in the judicial system (Ginezi 2012;Silveira 2022; Santos 2016, 2020; Pinheiro 2020; Santos 2022). Through a qualitative approach,semi-structured interviews were conducted, along with analysis of some laws and documents found on the TJTO website and recommendations made by the National Council of Justice (CNJ). The results show progress in the implementation of the service, such as the presence of TILSP in all court sessions and events, physical adjustments for the transmission of virtual sessions, the inclusion of TILSP as sworn public translators, and the recognition of deaf individuals as accredited professionals. Additionally, adaptations were made to the Sworn Translator notice, allowing the accreditation of deaf translators and interpreters. However, challenges remain, such as the growing demand for services, the need for TILSP training to better understand legal terminology and procedures involving the legal sphere, and the need for continuous improvements in the quality of service offered, especially regarding the outsourcing of some translation and interpretation services in Civil and Criminal Chambers, as well as in the Full Court.